Habilidades auditivas em adultos normo-ouvintes bilíngues e monolíngues - Oppitz, Sheila Jacques (2016)
Bilingualism is becoming more common in world and, despite being much discussed their impact on the language, there s not much knowledge about the effect of different linguistic backgrounds in auditory processing skills. We know that, when a person is exposed to two languages, it increases speed and efficiency of information processing and, therefore, bilingual subject is benefited in development and recognition of patterns of important sounds for speech understanding. Investigate and compare performance of auditory skills in normal hearing adults with different levels of late bilingualism between them, and normal hearing monolingual people using behavioral and electrophysiological tests.This study is descriptive, quantitative and transversal. The sample was consisted of 65 subjects (Monolingual Group (MG) with 13 speakers of Portuguese; Teachers group (GT): 13 bilingual language - schools teachers - (Portuguese - English) and language school students at different levels of proficiency (Portuguese-English): 13 at advanced level (AG); 13 at intermediate level (IG); 13 at basic level (BG)) with normal hearing and no complaints about auditory processing abilities, aged 18-35 years. They were subjected to behavioral tests: Staggered Spondaic Word test (SSW), which evaluates attention skills, memory and figure-ground for verbal sounds; Random Gap Detection Test (RGDT) that assesses ability of temporal resolution; and electrophysiological test Long Latency Auditory Evoked Potential (LLAEP) with verbal stimuli (syllables / ba / - frequent stimulus and / di / - rare stimulus) evaluating memory, attention and auditory discrimination. In a general way, in analysis between groups, there were significant differences with higher values to age, SSW and lower values to RGDT for teachers, compared with monolinguals. Comparing students at different levels of English learning, there were higher values for RGDT and latency of component N1 for basic level of proficiency. Late bilinguals people have further development of attention ability and auditory memory, when compared to monolingual ones. In addition to that, there is an improvement in temporal resolution ability as English learning level increases.